Proceedings of the Tenth International Conference on Learning Analytics &Amp; Knowledge 2020
DOI: 10.1145/3375462.3375530
|View full text |Cite
|
Sign up to set email alerts
|

Data-informed curriculum sequences for a curriculum-integrated game

Abstract: In this paper, we perform a predictive analysis of a curriculumintegrated math game, ST Math, to suggest a partial ordering for the game's curriculum sequence. We analyzed the sequence of ST Math objectives played by elementary school students in 5 U.S. districts and grouped each objective into difficult and easy categories according to how many retries were needed for students to master an objective. We observed that retries on some objectives were high in one district and low in another district where the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Research has shown that teaching with games increases students' academic achievement (Divjak & Tomić, 2011;Karamert, 2019;Pehlivan, 2020;Türkmen, 2017) and positively affects their attitudes toward mathematics ( Tükle, 2020), and that research participants have a positive attitude toward the use of games in mathematics courses (Koç-Deniz, 2019;Russo et al, 2021;Watson-Huggins, 2018).These results are in line with previous research studies conducted on this subject (Divjak & Tomic, 2011;Turgut & Temur, 2017;Türker & Arslan, 2021). However, in studies where negative effects were observed, it was found that teachers were not aware of the use of games in mathematics teaching (Pilten, Pilten, Divrik & Divrik, 2017) and that there was a lack of harmony between technological games and pedagogical principles ( Lindström, Gulz, Haake & Sjödén, 2011).In addition, results are also included on teachers' need for game materials (Kondratieva & Freiman, 2011), the low use of games in some countries (Nabie, 2008), some needs for integrating game use into the curriculum (Akintunde et al, 2020;Callaghan, Long, van Es, Reich, & Rutherford, 2017;Fouze & Amit, 2018;Graceota & Slamet., 2021;Koneva & Shabanova, 2021;Shabrina et al, 2020), the effects of designing game components and the effects of game design (Ke, 2014;Rawansyah et al, 2021;Trujillo, Chamberlin, Wiburg & Armstrong, 2016), and the inappropriateness of using games according to certain standards (NCTM) (Joung & Byun, 2020). To eliminate some negative situations, it is recommended that the Ministry of National Education act as a problem solver, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that teaching with games increases students' academic achievement (Divjak & Tomić, 2011;Karamert, 2019;Pehlivan, 2020;Türkmen, 2017) and positively affects their attitudes toward mathematics ( Tükle, 2020), and that research participants have a positive attitude toward the use of games in mathematics courses (Koç-Deniz, 2019;Russo et al, 2021;Watson-Huggins, 2018).These results are in line with previous research studies conducted on this subject (Divjak & Tomic, 2011;Turgut & Temur, 2017;Türker & Arslan, 2021). However, in studies where negative effects were observed, it was found that teachers were not aware of the use of games in mathematics teaching (Pilten, Pilten, Divrik & Divrik, 2017) and that there was a lack of harmony between technological games and pedagogical principles ( Lindström, Gulz, Haake & Sjödén, 2011).In addition, results are also included on teachers' need for game materials (Kondratieva & Freiman, 2011), the low use of games in some countries (Nabie, 2008), some needs for integrating game use into the curriculum (Akintunde et al, 2020;Callaghan, Long, van Es, Reich, & Rutherford, 2017;Fouze & Amit, 2018;Graceota & Slamet., 2021;Koneva & Shabanova, 2021;Shabrina et al, 2020), the effects of designing game components and the effects of game design (Ke, 2014;Rawansyah et al, 2021;Trujillo, Chamberlin, Wiburg & Armstrong, 2016), and the inappropriateness of using games according to certain standards (NCTM) (Joung & Byun, 2020). To eliminate some negative situations, it is recommended that the Ministry of National Education act as a problem solver, e.g.…”
Section: Discussionmentioning
confidence: 99%